Deutsch im Blick - Abrams, Zsuzsanna (Open textbook library., 2017)
This textbook includes all 10 chapters of Deutsch im Blick. It accompanies http://coerll.utexas.edu/dib/, the web-based first-year German program developed and in use at the University of Texas since 2008, and its companion site, Grimm Grammar. Deutsch im Blick is an open access site with free and open multimedia resources, which requires neither password nor fees. Deutsch im Blick has been funded and created by Liberal Arts Instructional Technology Services at the University of Texas, and is currently supported by COERLL, the Center for Open Educational Resources and Language Learning UT-Austin, and the U.S. Department of Education Fund for the Improvement of Post-Secondary Education (FIPSE Grant P116B070251 & P116Y090057) as an example of the open access initiative.